Phytochemical Screening and Antihyperglycemic Activity of Basella rubra - Journals, A. Nirmala1*, S. Saroja2; S. Gayathri (Recent Research in Science and Technology, 2011)
The objective of the present study was phytochemical screening andÃ‚Â antihyperglycemic activity of Aqueous extract of Basella rubra Ã‚Â in streptozotocin-induced diabetic rats. The phytochemical screening of Basella rubra was done by using different methods. Basella rubra is found to contain high levels of the non-enzymic ,enzymic antioxidants, and Phytonutrients it would be effective in treating the diseases caused by free radicals and also in the treatmentÃ‚Â of diabetes. The STZ induced diabetic rats are divided into four groups of six animals each. Group I served as Non diabetic control, Group II - Diabetic control, Group III Non-diabetic rats treated with Basella rubra, Group IV Diabetic rats treated with Basella rubra. The Aqueous extract of Basella rubra produced a significant antihyperglycemic (decrease in blood glucose level) effect (p<0.05) after the treatment, and decreased level of fructosamine .The findings of the present study suggest that it is rich in phytonutrients, it includes the enzymic and nonenzymic antioxidant. Basella rubra being a good source of these enzymes may be effective in the treatment of hyperglycemia .From this study it was concluded thatÃ‚Â aqueous extract of Basella rubra produced significant antihyperglycemic activity in STZ induced diabetic rat which is comparable to control rat.